COOPERATION OF REGIONAL MILITARY COMMAND III/SILIWANGI WITH REGIONAL GOVERNMENTS IN ACCELERATING COVID-10 VACCINATION IN THE PROVINCE OF WEST JAVA, INDONESIA - Agus Subagyo; Anggun Dwi Panorama (Universitas Jenderal Ahmad Yani, 2023)
This study aims to analyze the cooperation of the III/Siliwangi Regional Military Command in assisting the West Java Provincial Government to accelerate the covid-19 vaccination since January 2021. The research question is how the III/Siliwangi Military Regional Command cooperates with the Regional Government in accelerating the covid-19 vaccination program in the Province West Java? In answering these questions, the analytical framework of cooperation theory is used, where cooperation carried out by two or more parties to achieve certain goals will be successful if it goes through the stages of communication, coordination, and collaboration. The research method used is a qualitative method with data collection techniques using interviews, observation, and documentation studies. The results of the study found that the cooperation carried out by the Regional Military Command III/Siliwangi with the Regional Government in accelerating the covid-19 vaccination was realized through the following stages: (1) Communication, namely holding formal and informal meetings with regional heads, both governors, regents, and mayors to discuss vaccination plans; (2) Coordination, namely holding a coordination meeting for regional leaders to discuss the division of tasks in the vaccination program; (3) Collaboration, namely carrying out joint actions to hold vaccinations with the theme: